Saturn's Small‐Scale Winds Revealed by Its High‐Degree Gravity Field - S. Kim; M. Parisi; C. R. Mankovich; D. R. Buccino; O. Yang (Geophysical Research Letters)
Abstract During its Grand Finale, the Cassini spacecraft collected crucial gravity data, revealing Saturn's low‐degree gravity harmonics and large‐scale zonal winds extending about 8,000 km deep. However, determining the high‐degree gravity field, essential for understanding small‐scale atmospheric dynamics, is challenging due to the limited spatial coverage of Cassini's periapses. To overcome this limitation, we employed Slepian functions, orthogonal within a bounded domain, to represent Saturn's localized high‐degree gravity field. Focusing on latitudes from 32°S to 32°N, we estimated Slepian coefficients that represent short‐scale latitudinal gravity variations. The reconstructed wind profile that explains low‐degree harmonics can also reproduce these high‐degree variations, assuming Saturn's atmosphere is, to first order, in thermal wind balance. Our findings suggest that small‐scale winds may extend to depths between 7,000 km and 9,000 km, providing strong evidence that Saturn's zonal flows are oriented along coaxial cylinders, rotating at different angular velocities.